Differentiation of Papillary Muscle From Fascicular and Mitral Annular Ventricular Arrhythmias in Patients With and Without Structural Heart Disease. (June 2015) - Al'Aref, Subhi J.; Ip, James E.; Markowitz, Steven M.; Liu, Christopher F.; Thomas, George; Frenkel, Daniel; Panda, Nikhil C.; Weinsaft, Jonathan W.; Lerman, Bruce B.; Cheung, Jim W.
Abstract : Background—: Idiopathic left ventricular arrhythmias (VAs) and those caused by structural heart disease can originate from the papillary muscles, fascicles, and mitral annulus. Differentiation of these arrhythmias can be challenging because they present with a right bundle branch block morphology by electrocardiography. We sought to identify clinical, electrocardiographic, and electrophysiological features that distinguish these left VAs in patients with and without structural heart disease. Method and Results—: Patients undergoing catheter ablation for papillary muscle, fascicular, or mitral annular VAs were studied. Demographic data and electrocardiographic and electrophysiological findings were analyzed. Fifty-two VAs in 51 patients (32 [63%] male; mean age 61±15 years) with papillary muscle (n=18), fascicular (n=15), and mitral annular (n=19) origins were studied. Patients with papillary muscle VAs were older and had higher prevalence of left ventricular dysfunction (67% versus 13% of fascicular VA patients [ P =0.009]) and coronary artery disease (78% versus 37% of mitral annular VA patients [ P =0.036]). Papillary muscle VAs were distinguished electrocardiographically from fascicular VAs by longer QRS durations and lower prevalence of r1 QRS morphology, and from mitral annular VAs by lower prevalence of positive precordial lead concordance. Using a stepwise electrocardiographic algorithm, the accuracy rates for the diagnosis of papillary muscle VAs, fascicular VAs, and mitral annular VAs were 83%, 87%, and 89%, respectively. Conclusions—: Specific electrocardiographic characteristics, including QRS morphology and precordial lead morphology, can help distinguish between papillary muscle, fascicular, and mitral annular VAs. Abstract : Supplemental Digital Content is available in the text.